Effect of Token Economy Therapy for Reducing Attachment Behavior Among Pre-School Children in Kindergarten - Ramaita .; Purba, J.M; Putri, D.E. (Faculty of Nursing, Universitas Andalas, 2018)
Background: Attachment behaviors are behaviors experienced by children when they would leave their homes and families to join his friends at school he regarded as strangers. This behavior can interfere with the functioning life of the child so that the child can not be independent, and parents should be involved more in the activities of children. Purpose: To determine the effect of economic token therapy for reducing the attachment behavior among Kindergarten Students. Method: The design of this study was quasi experimental with pre and post with control group. By using multistage random sampling and consecutive sampling technique with a total sample of 68 people who experienced attachment behavior. Consisted of 34 peoples as intervention group and 34 peoples as control group. Bivariate analysis using Wilcoxon test and mann-whitney test. Results: The results showed that there were significant differences of attachment behavior before and after entering the token economy intervention in the intervention group compared with those in the control group (p = 0.000). Conclusion: Token economy therapy has positive effect to reduce attachment behavior of kindergarten student at the beginning of learning process in the kindergarten school. The application of economic token is recommended to overcome the attachment behavior of existing preschool children in schools and in the general public health services.